2015
DOI: 10.17221/141/2014-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rootstocks on different sweet cherry cultivars and accumulation of heavy metals in leaves and fruit

Abstract: Two seedling rootstocks of Mahaleb cherry (Prunus mahaleb L.) from a German type cv. Alpruna marked as No. 2 and No. 6 were selected for their semi-dwarfing properties from biotypes growing at the Rural Experimental Station in Baranowo belonging to the University of Life Sciences in Poznan, Poland. In an orchard experiment in 2012-2013, growth and yield of eight-and nine-year old trees of the cvs Regina, Summit and Vanda were studied. These cultivars were grafted on Mahaleb cherry No. 2 and No. 6 and were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Cd contamination in orchard soil could inhibit net photosynthesis, decrease chlorophyll, repress plant growth, alter carbohydrate concentrations, limit fruit cultivation, and poses a threaten to human health (Hamurcu et al, 2010; López-Climent et al, 2011; Podazza et al, 2012; Stachowiak et al, 2015; Wang et al, 2015b). Clean-up of Cd-contaminated soil is quite difficult and expensive which usually takes several years, or even decades (McGrath and Zhao, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cd contamination in orchard soil could inhibit net photosynthesis, decrease chlorophyll, repress plant growth, alter carbohydrate concentrations, limit fruit cultivation, and poses a threaten to human health (Hamurcu et al, 2010; López-Climent et al, 2011; Podazza et al, 2012; Stachowiak et al, 2015; Wang et al, 2015b). Clean-up of Cd-contaminated soil is quite difficult and expensive which usually takes several years, or even decades (McGrath and Zhao, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The application of urban composts, metal-based pesticides, ripening agents, and fertilizers and wastewater irrigation have resulted in increasing cadmium (Cd) accumulation in orchard soil of many parts of the world especially in developing countries (Andreu and Gimeno-García, 1996 ; Pinamonti et al, 1997 ; Li et al, 2014 ; Wang et al, 2015b ; Duan et al, 2016 ). Cd contamination in orchard soil could inhibit net photosynthesis, decrease chlorophyll, repress plant growth, alter carbohydrate concentrations, limit fruit cultivation, and poses a threaten to human health (Hamurcu et al, 2010 ; López-Climent et al, 2011 ; Podazza et al, 2012 ; Stachowiak et al, 2015 ; Wang et al, 2015b ). Clean-up of Cd-contaminated soil is quite difficult and expensive which usually takes several years, or even decades (McGrath and Zhao, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the rootstock affects heavy metal accumulation and translocation to the shoots (Stachowiak et al, 2016). Cd deposition in the root restricts the translocation of the metal to the shoot.…”
Section: Tolerance and Accumulation Is Mediated By Both Rootstock mentioning
confidence: 99%
“…Cd is a non-essential and highly phytotoxic element. It impairs root function, inhibits nutrient uptake and assimilation, impedes photosystem II activity, lowers carbohydrate concentrations, hinders protein synthesis, suppresses plant growth, and limits fruit yield ( Lopez-Climent et al., 2011 ; Stachowiak et al., 2016 ). Cd accumulation in edible plant parts may ultimately enter the human body via the food chain and poses a serious threat to human health ( Nawrot et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium is a widespread industrial and environmental pollutant that may cause adverse effects on human beings and animals. Major anthropogenic sources of cadmium exposure to human are mining, electrodes of rechargeable batteries, alloys production, tobacco smoking, electroplating, plastic stabilizers, vapor lamps, engraving, fertilizers and old galvanized PVC water supply pipes (Duan et al, 2016, Stachowiak et al, 2015). In Present Scenario discarded electronic materials and their components have arisen as the biggest source of Cadmium exposure.…”
Section: Introductionmentioning
confidence: 99%